A BRIEF REVIEW ON THE CEMENTAL TEAR: IS IT AN ENDODONTIC OR PERIODONTAL PROBLEM? - Herbert Mario Gallegos Vargas (2024)
This article presents an overview of the causes of cemental tear, which is characterized by the partial or total separation of a part of the cementum lining the root. Radiographic examinations are used to diagnose cemental tear indicating a radiopaque fragment of cement partially or totally separated from the root.  As cemental tear can be associated with both endodontic (root canal) and periodontal (gum and bone) problems, the choice of the treatment method has been based on the according the location and level of the fragment. Several studies have showed that cemental tear problem is mainly caused by the periodontal disease, which not having been properly diagnosed and consequently non-treated allowed the recurrence. The literature shows that the success of the treatment is directly related to the removal of the fragment and polishing of the root.  In this brief review article, we report the key causes of cemental tear discussing if it is an endodontic or periodontal problem.